The Role of Passives Smoking in the Occurrence of Acute Otitis Media - Nezamoddin Berjis; Zahra Abdeyazdan; Seyed Ahmadreza Okhovat; Nazanin Gholami Ghasri; Ali Salem (مجله دانشکده پزشکی اصفهان, 2011)
Background: Acute otitis media is a common childhood disease with high cost in each community. Therefore, recognition of predisposing factors for acute otitis media has significant role in prevention of it and is cost-effective. There is conflicting results in previous studies for role of passive smoking in acute otitis media. The present study was designed to compare frequency of smoking in family of children with acute otitis media with control group. Methods: In a cross sectional case-control study, 90 children aged 7-12 years with acute otitis media were selected by simple convenient method and compared with 90 children who had not acute otitis media; both groups were matched for age and gender. Data were analyzed by SPSS (chi square test and logistic regression). P value less than 0.05 considered as significant. Finding: The frequency of smoking among family members of children with acute otitis media was significantly more than the relative of children without it. The odds ratio for passive smoking was 1.85. In other words, there was a significant correlation between passive smoking and occurrence of acute otitis media. Conclusion: In the present study, occurrence of acute otitis media was more than many studies carried out in other countries. This can be due to race differences between communities as an independent factor. To know risk factors of acute otitis media, it is recommended carrying out more studies with larger sample sizes in our community.